Genomic Mutation Profile of Primary Gastrointestinal Diffuse Large B-Cell Lymphoma - Li, Peifeng; Chai, Jia; Chen, Zi; Liu, Yang; Wei, Jie; Liu, Yixiong; Zhao, Danhui; Ma, Jing; Wang, Kaijing; Li, Xia; Shao, Yang; Gong, Li; et al. (Frontiers in Oncology, 2021)
Primary gastrointestinal diffuse large B-cell lymphoma (GI-DLBCL) is the most common gastrointestinal lymphoma, but its genetic features are poorly understood. We performed whole-exome sequencing of 25 primary tumor samples from patients with GI-DLBCL and 23 matched normal tissue samples. Oncogenic mutations were screened, and the correlations between genetic mutations and clinicopathological characteristics were analyzed. Twenty-five patients with GI-DLBCL were enrolled in the genetic mutation analysis with a median of 184 (range 79-382) protein-altering variants per patient. We identified recurrent oncogenic mutations in GI-DLBCL, including those in TP53, MUC16, B2M, CCND3, HIST1H1C, NEB, and ID3. Compared with nodal DLBCL, GI-DLBCL exhibited an increased mutation frequency of TP53 and reduced mutation frequencies of PIM1, CREBBP, BCL2, KMT2D and EZH2. Moreover, GI-DLBCL exhibited fewer MYD88 and CD79B mutations than DLBCL in the testis and central nervous system. GI-DLBCLs with HLA-B, MEF2A, RHOA and NAV3 mutations exhibited a tendency toward a high proliferation index. MUC16 and ETV6 mutations often occurred in tumors with early clinical staging. Our data provide a comprehensive understanding of the landscape of mutations in a small subset of GI-DLBCLs. The genetic mutation profiles of GI-DLBCL differ from those of nodal DLBCL and DLBCL in immune-privileged sites. The different mutated genes are related to the NF-κB and JAK-STAT pathways, and the different pathogenetic mechanisms leading to the development of DLBCL are most likely dependent, at least in part, on the tissue microenvironment. Differences in genetic alterations might influence the clinicopathological characteristics of GI-DLBCL.